Prediksi Pelaku Perjalanan Luar Negeri Di Masa Pandemi COVID-19 Menggunakan Metode Regresi Linier Sederhana - Dewi Rahmawati; Titus Kristanto; Brian Freega Setya Pratama; Daninsyah Bagas Abiansa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Indonesia is a country that has natural beauty and cultural diversity, making tourists from abroad visit Indonesia. The purpose of tourists coming to Indonesia is to travel with their families. Over time, tourists or foreign travellers have decreased, due to the COVID-19 outbreak in Indonesia that has not ended. As a result of the COVID-19 outbreak, several airports and ports were temporarily closed to avoid the development of an increasingly virulent COVID-19. The purpose of the study was to determine the prediction of the number of arrivals of foreign travelers using the linear regression method. The simple linear regression method is a method consisting of one or more ordinary independent variables with the notation X and one dependent variable represented by the notation Y. The independent variable is the number of foreign travelers to Indonesia as notation X and the dependent variable is the number of COVID-19 cases in Indonesia. Indonesia as Y notation.